Psychological wellbeing pada anggota TNI – AD: Menguji peran iklim organisasi dan psychological capital - Pratiwi, Dicha Berliana; Sofiah, Diah; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2023)
The purpose of this study was to determine the relationship between organizational climate and psychological capital on the psychological well-being of members of the TNI - AD Zidam V Brawijaya. This study used a random sampling technique and involved 170 respondents. The results of the study used the Spearman rank analysis test. The results of the correlation test between organizational climate variables and psychological well-being are expressed as correlations. So the higher the organizational climate, the higher the psychological well-being. The results of the correlation test between the variables of psychological capital and psychological well-being are expressed as a correlation. So the higher the individual's psychological capital, the higher the psychological well-being. Seeing from these results stated that there is a positive relationship between organizational climate with psychological well-being and psychological capital with psychological well-being. Tujuan penelitian ini adalah untuk mengetahui hubungan antara iklim organisasi dan psychological capital terhadap psychological well-being Anggota TNI – AD Zidam V Brawijaya. Penelitian ini menggunakan teknik random sampling dan melibatkan 170 responden. Hasil penelitian menggunakan uji analisis rank spearman. Hasil uji korelasi antara variable iklim organisasi dengan psychological well-being dinyatakan korelasi. Maka semakin tinggi iklim organisasi semakin tinggi pula psychological well-being. Hasil uji korelasi antara variable psychological capital dengan psychological well-being dinyatakan korelasi. Maka semakin tinggi psychological capital individu maka semakin tinggi pula psychological well-being. Melihat dari hasil tersebut menyatakan bahwa ada hubungan positif antara iklim organisasi dengan psychological well-being dan psychological capital dengan psychological well-being.